Ancient Jewish sciences and the history of knowledge in Second Temple literature - Ben-Dov, Jonathan; Sanders, Seth L. (New York University Press, 2014)
Until very recently, the idea of ancient Jewish sciences would have been considered unacceptable. Since the 1990's, Early Modern and Medieval Science in Jewish sources has been actively studied, but the consensus was that no real scientific themes could be found in earlier Judaism. This work points them out in detail, and posits a new field of research: the scientific activity evident in the Dead Sea Scrolls and Early Jewish Pseudepigrapha. The publication of new texts and new analyses of older ones reveals crucial elements that are best illuminated by the history of science, and may have inte.